Leighton W. Rogers papers - Rogers, Leighton W. (Leighton William), 1893-1962.
Correspondence, diary (1916 September-1919 April), autobiographical sketch, writings, obituaries, scrapbooks, and a map documenting Rogers's studies at Dartmouth College (1912-1916); experiences in Saint Petersburg, Russia, as an employee of the National City Bank of New York (1916-1918); service as an intelligence officer in Great Britain and France for the American Expeditionary Forces (1918-1919), as a trade commissioner in Europe (1921-1926) representing the Aeronautics Trade Division of the U.S. Dept. of Commerce, as president of the Aeronautical Chamber of Commerce of America (1926-1936), and as a representative on missions to Japan and China for the transportation committee of the American Economic Mission to the Far East (1935); his mission (1943-1944) to the Soviet Union on behalf of the U.S. Army Air Forces to obtain information vital to the Allied war effort; and his life as a consultant in Connecticut. Includes his writings on the Soviet theater and other writings presenting an American's perspective on the Russian revolution and Soviet life.
Aeronautical executive, army officer, and public official. Also known as Leigh Rogers.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aeronautical Chamber of Commerce of America; Allied Forces; American Economic Mission to the Far East; Dartmouth College -- Students; National City Bank of New York; United States. -- Army. -- American Expeditionary Forces; United States. -- Army Air Forces; United States. -- Department of Commerce. -- Aeronautics Trade Division; Aeronautics; Banks and banking -- Russia (Federation) -- Saint Petersburg; Consultants -- Connecticut; Theater -- Soviet Union; Transportation -- China; Transportation -- Japan; World War, 1914-1918 -- Military intelligence -- France; World War, 1914-1918 -- Military intelligence -- Great Britain; World War, 1939-1945 -- Military intelligence -- Soviet Union; China -- Economic conditions -- 1912-1949.; Japan -- Economic conditions -- 1918-1945.; Saint Petersburg (Russia) -- History -- Revolution, 1917-1921.; Soviet Union -- History -- Revolution, 1917-1921.; Soviet Union -- Social life and customs; United States -- Commerce -- Europe; United States -- Commerce -- Russia; United States -- Commerce -- Soviet Union; Army officers; Executives; Public officials